Comparison among Neuroblastoma Stages Suggests the Involvement of Mitochondria in Tumor Progression - Stefano Cagnin; Tomas Knedlik; Caterina Vianello; Ana Paula Magalhães Rebelo; Agnese De Mario; Marta Giacomello (Biomedicines, 2023)
Neuroblastoma (NB) is the most common extracranial tumor of early childhood and accounts for 15% of all pediatric cancer mortalities. However, the precise pathways and genes underlying its progression are unknown. Therefore, we performed a differential gene expression analysis of neuroblastoma stage 1 and stage 4 + 4S to discover biological processes associated with NB progression. From this preliminary analysis, we found that NB samples (stage 4 + 4S) are characterized by altered expression of some proteins involved in mitochondria function and mitochondria–ER contact sites (MERCS). Although further analyses remain necessary, this review may provide new hints to better understand NB molecular etiopathogenesis, by suggesting that MERCS alterations could be involved in the progression of NB.